Changes in ferroelectric properties of barium titanate ceramic with compressive stress - Wanwilai Chaisan (2018)
In this work, barium titanate (BT) ceramic was prepared using a conventional mixed oxide method. The effect of uniaxial compressive stress on the ferroelectric properties of BT ceramics were investigated. The changes in ferroelectric properties were observed at stress up to 60 MPa using a compressometer in conjunction with a modified Sawyer-Tower circuit. The results showed that applied stress had a significant influence on the ferroelectric properties of BT ceramics. Ferroelectric characteristics, i.e. the area of the ferroelectric hysteresis (P-E) loop, the saturation polarization (P sat), the remanent polarization (Pr) and the loop squareness (Rsq), decreased with increasing compressive stress, while the coercive field (Ec) remained constant. Stress-induced domain wall motion suppression and non-180° ferroelectric domain switching processes are responsible for the changes observed. © 2007 The Royal Swedish Academy of Sciences.